The progress of fuel cell for malaysian residential consumption: Energy status and prospects to introduction as a renewable power generation system - Zakaria Z.; Kamarudin S.K.; Abd Wahid K.A.; Abu Hassan S.H. (Elsevier Ltd, 2023)
Electric power generation; Electric power transmission; Energy resources; Housing; Population statistics; Portable equipment; Energy status; Global population; Malaysia; Malaysians; Population growth; Portable device; Renewable power generation systems; Residential application; Residential consumption; Status and prospect; Fuel cells